Primer reporte de cuatro especies de escarabajos coprófagos (Coleoptera: Scarabaeinae) en El Salvador - Pablo-Cea, José D.; Velado-Cano, Maryory A.; Solís, Ángel (Instituto de Ecología, A.C., 2016)
We present the first records of four species of Scarabaeinae: Canthidium pseudopuncticolle, Canthon femoralis, Uroxys deavilai and Uroxys microcularis, in El Salvador. We collected the specimens, using feces and carrion baited traps in three zones in the National Park El Imposible in the Southwest of the country. With this report, we contribute to the knowledge of the dung beetle fauna of El Salvador.